Phosphite determination in fertilizers after online sequential sample preparation in a flow injection system - Roberta Dametto, Patricia; Pezza Franzini, Vanessa; Gomes Neto, José Anchieta [UNESP] (Amer Chemical Soc, 2007)
A flow injection spectrophotometric system is proposed for phosphite determination in fertilizers by the molybdenum blue method after the processing of each sample two times on-line without and with an oxidizing step. The flow system was designed to add sulfuric acid or permanganate solutions alternately into the system by simply displacing the injector-commutator from one resting position to another, allowing the determination of phosphate and total phosphate, respectively. The concentration of phosphite is obtained then by difference between the two measurents. The influence of flow rates, sample volume, and dimension of flow line connecting the injector-commutator to the main analytical channel was evaluated. The proposed method was applied to phosphite determination in commercial liquid fertilizers. Results obtained with the proposed FIA system were not statistically different from those obtained by titrimetry at the 95% confidence level. In addition, recoveries within 94 and 100% of spiked fertilizers were found. The relative standard deviation (n = 12) related to the phosphite-converted-phosphate peak alone was <= 3.5% for 800 mg L-1 P (phoshite) solution. Precision due to the differences of total phosphate and phosphate was 1.1% for 10 mg L-1 P (phosphate) + 3000 mg L-1 P (phosphite) solution. The sampling rate was calculated as 15 determinations per hour, and the reagent consumption was about 6.3 mg of KMnO4, 200 mg of (NH4)(6)Mo7O24 center dot 4H(2)O, and 40 mg of ascorbic acid per measurement.
Keywords: fertilizer; phosphite; FIA; spectrophotometry